Tindak Tutur Ilokusi dalam Gelar Wicara Mengenai Teori Konspirasi Covid-19 - Rismaya, Rima; Suganda, Dadang (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This research is a qualitative descriptive study which was conducted to describe illocutionary speech acts in a speech title regarding the Covid-19 conspiracy theory. Collecting data in this study using the observation method with note-taking techniques. The data source of this research is a speech in a video talk show about the accusation of conspiracy behind Corona which is broadcast on the Kompastv Youtube channel. The data analysis of this study used an extratextual matching method with a pragmatic approach. The theory of various illocutionary speech acts used in this study is Searle's (1979) illocutionary speech act theory. The results showed that there were four types of illocutionary speech acts in the research sources, namely assertive, directive, commissive, and expressive speech.